Knowledge structure and future research trends of body–mind exercise for mild cognitive impairment: a bibliometric analysis - Zhang, Jing; Yang, Zhen; Fan, Huiying (Frontiers in Neurology, 2024)
Background Mild cognitive impairment (MCI) is a common neurodegenerative disorder that poses a risk of progression to dementia. There is growing research interest in body–mind exercise (BME) for patients with MCI. While we have observed a rapid growth in interest in BME for MCI over the past 10 years, no bibliometric analysis has investigated the knowledge structure and research trends in this field. Consequently, the objective of this research is to conduct a bibliometric analysis of global publications of BME for MCI from 2013 to 2022. Methods A total of 242 publications in the field of BME for MCI were retrieved from the Web of Science Core Collection. Bibliometric analysis, including performance analysis, science mapping, and visualization, was performed using CiteSpace, VOSviewer, and Microsoft Excel. Results Publications and citations in the field of BME for MCI have shown a rapidly increasing trend over the last decade. Geriatrics & Gerontology, and Neurosciences were the most frequently involved research categories. China (78 documents) and the USA (75 documents) contributed to the largest number of publications and had the strongest international collaborative networks. Fujian University of Traditional Chinese Medicine contributed to the largest number of publications (12 documents), and Chen, L of this institution was the most prolific author (12 documents). Frontiers in Aging Neuroscience (16 documents), and JOURNAL OF ALZHEIMER’S DISEASE (12 documents) were the most prolific journals. Tai Chi and Baduanjin, as specific types of BME, were the hotspots of research in this field, while evidence synthesis and guidelines might be future research trends. Conclusion In the last decade, there has been a rapid growth in scientific activities in the field of BME for MCI. The results of this study provide researchers and other stakeholders with knowledge structure, hotspots, and future research trends in this field.